Fractal Characteristics of Discontinuous Growth of Digital Company: An Entrepreneurial Bricolage Perspective - Xiaoyu Yu; Jiangyong Lu; Xiaomin Liu; Yihan Wang; Yilin Jia (Complexity)
Digital companies exhibit discontinuous growth in the process of shifting from their existing core business to a newer and less familiar business. This pattern of growth often ends in failure mainly because companies invest most of their resources in maintaining the value network of their existing core business, which ultimately results in a “lock-in” effect. The fractal theory assumes that there are similarities among fractals within companies. These similarities may reduce the threats posed by the value network lock-in effect and increase the chances of successful discontinuous growth. In this study, we applied fractal theory to consider the following questions: (1) in what aspects does the successful discontinuous growth of digital companies exhibit fractal characteristics? (2) What strategy does digital companies use to ensure these fractal characteristics? We adopted an exploratory single-case study method and chose ByteDance as the case company to analyze its successful shift from Toutiao (a media platform) to Douyin (a short-video sharing platform). Our results show that (1) a necessary condition for the successful discontinuous growth of digital companies is that similarities exist (e.g., in technology or customer base) between the existing core business and the new business and (2) entrepreneurial bricolage is a strategy used by digital companies to ensure the existence of fractal characteristics of similarities. We discuss the theoretical contributions and practical implications of this finding.